Optimization of Digital Technology Utilization in Marketing Strategy Development to Enhance the Competitiveness of MSME Products - Rachmiani Rachmiani; Naufal Haidar Ahmada; Darusman Darusman (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2025)
This study aims to analyze the impact of digital technology on marketing strategy development and its effect on the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. In an era of rapid digitalization, adopting digital technology has become a crucial factor in enhancing the competitiveness of MSMEs. The research utilizes a quantitative approach with a survey design, where data was collected through questionnaires distributed to 100 MSME entrepreneurs who have integrated digital technology into their marketing strategies. The findings indicate that using social media and e-commerce platforms significantly contributes to increased brand awareness, sales, and customer loyalty for MSMEs. Approximately 68% of respondents reported a sales boost after utilizing digital platforms, while more than 60% noted enhanced brand visibility. On the other hand, despite the great potential of SEO and email marketing to improve competitiveness, the application of these strategies remains limited. Multiple linear regression analysis suggests that the more intensively digital technology is used, the greater the competitiveness of MSME products in an increasingly competitive market. These findings emphasize the importance of integrating digital technology into MSME marketing strategies to strengthen their position in domestic and global markets. Therefore, MSME entrepreneurs are encouraged to expand their understanding and implementation of additional digital marketing strategies and seek more significant support from the government and related institutions.